Psychological interventions to reduce alcohol consumption recommended by modern clinical guidelines (review of foreign publications) - Lisna, Natalia M. (Psychiatry, Neurology and Medical Psychology, 2020)
The article presents the data of theoretical analysis of modern approaches to solving the problem of alcohol abuse; it is stated that harmful alcohol consumption will remain a global problem in the future, given the current trends in health, culture and the market around the world. The need to introduce effective and cost-effective strategies and measures to prevent and reduce the harm associated with alcohol abuse in accordance with national priorities and contexts is substantiated. The main stages of treatment are identified, namely: diagnostic and motivational (includes physical examination, choice of treatment program, conclusion of a written therapeutic agreement), detoxification (pharmacological treatment of withdrawal, strengthening the patient’s motivation for further treatment), treatment of addiction syndrome (individual / group psychotherapist), symptomatic therapy), medical and social rehabilitation (supportive psychotherapy, social work). The most appropriate and effective psychotherapeutic approaches recommended by modern clinical protocols for the treatment of alcohol dependence in developed countries, including: behavioral therapy for couples (BCT), brief psychological interventions (BPI), family counseling (BSFT), cognitive-behavioral therapy (CBT), contingency management (CM), motivational therapy / motivational interviewing (MT), psychodynamic psychotherapy (PT), 12-step psychotherapy (AA). It is confirmed that the integration of psychotherapeutic and pharmacological approaches is supported in clinical guidelines for the treatment of alcohol dependence. It is concluded that improving organizational approaches to anti-alcohol therapy through the use of advanced technologies with proven effectiveness — on the one hand, as well as expanding international cooperation and adequate policy decisions — on the other hand, will reduce alcohol consumption and its negative effects in our country.